COMBINING WLI AND SEM TECHNIQUES TO OBTAIN A 4D SURFACE IMAGE OF A ppHDMSO/AlCeO3 NANOCOMPOSITE - Buchheit, Olivier; Arnoult, Claire; Eddoumy, Fatima; Frari, Doriane Del; Martino, Jean Di; Ruch, David (Image Analysis and Stereology, 2011)
Compositional images from a SEM (scanning electron microscope) are sometimes complemented by quantitative topographical data from devices such as an AFM (atomic force microscope) or WLI (white light interferometer). Indeed, even if a SEM could provide both kinds of information (composition and topography), the topographical data are incomplete because the SEM does not allow measuring the vertical dimension (i.e., perpendicular to the measurement plane). Thus these two kinds of information are usually measured using two different techniques, and at different locations on the sample. Mean values of surface composition are then linked to mean values of topography, and as a consequence this approach does not allow precisely linking a local topographical peak to its corresponding composition. The present work deals with a SEM/WLI combination methodology, based on the characterization, at the same location, of a nanocomposite (nanoparticles of AlCeO3 dispersed in a plasma-polymerized hexamethyldisiloxane ppHMDSO matrix and deposited by atmospheric plasma on a glass substrate) developed for improving anticorrosion properties. SEM images allow the supposition that the protuberances (peaks) observed on the surface of a specimen are linked to the nanoparticles dispersed in the polymer coating, but this link is not fully convincing. Thanks to a precise localization method, SEM compositional data and WLI topographical data are here measured at the same location. The recombination of both signals to form a 4D image (3D geometry and 1D composition) allows linking protuberances to nanoparticles aggregates without ambiguity. This composite image appears to be an interesting new tool (at the scale of observation, i.e., hundreds of micrometers) for the study of nanostructured coatings.